Late onset sepsis and intestinal bacterial colonization in very low birth weight infants receiving long-term parenteral nutrition - Priscila Castro Cordeiro Fernandes; Elias Jose Oliveira von Dolinger; Vânia Olivetti Steffen Abdallah; Daiane Silva Resende; Paulo Pinto Gontijo Filho; Denise von Dolinger de Brito (Revista da Sociedade Brasileira de Medicina Tropical, 2011)
INTRODUCTION: The purpose of this study was to establish the late onset sepsis (LOS) rate of our service, characterize the intestinal microbiota and evaluate a possible association between gut flora and sepsis in surgical infants who were receiving parenteral nutrition (PN). METHODS: Surveillance cultures of the gut were taken at the start of PN and thereafter once a week. Specimens for blood culture were collected based on clinical criteria established by the medical staff. The central venous catheter (CVC) tip was removed under aseptic conditions. Standard laboratory methods were used to identify the microorganisms that grew on cultures of gut, blood and CVC tip. RESULTS: 74 very low birth weight infants were analyzed. All the infants were receiving PN and antibiotics when the gut culture was started. In total, 21 (28.4%) infants experienced 28 episodes of LOS with no identified source. Coagulase negative staphylococci were the most common bacteria identified, both in the intestine (74.2%) and blood (67.8%). All infections occurred in patients who received PN through a central venous catheter. Six infants experienced episodes of microbial translocation. CONCLUSIONS: In this study, LOS was the most frequent episode in neonates receiving parenteral nutrition who had been submitted to surgery; 28.6% of this infection was probably a gut-derived phenomenon and requires novel strategies for prevention.